Epidermal growth factor receptor detection in serum and saliva as a diagnostic and prognostic tool in oral cancer. (7th August 2017) - Zanotti, Laura; Paderno, Alberto; Piazza, Cesare; Pagan, Eleonora; Bignotti, Eliana; Romani, Chiara; Bandiera, Elisabetta; Calza, Stefano; Del Bon, Francesca; Nicolai, Piero; Ravaggi, Antonella
Abstract : Objectives/Hypothesis: Epidermal growth factor receptor (EGFR) is a type I transmembrane glycoprotein that is overexpressed in a wide variety of malignancies, including oral squamous cell carcinoma (OSCC). Our objective was to assess the EGFR diagnostic and prognostic value in OSCC by investigating its expression in serum and saliva of patients in comparison with healthy subjects. Study Design: Prospective case‐control study. Methods: Serum and saliva samples were collected from a cohort of 63 treatment‐naïve OSCC patients before surgery and a matched group of 60 healthy subjects. EGFR concentrations in serum and saliva were quantified by an enzyme‐linked immunosorbent assay. Results: OSCC patients showed lower values of serum EGFR compared with controls ( P = .0002). Conversely, saliva EGFR concentrations were higher in OSCC patients than in controls ( P = .0014). Saliva EGFR levels were also increased in patients with higher T category (pT4 vs. pT <4, median 6.0 vs. 3.8 ng/mL, P = .02). Considering 9.2 ng/mL (fourth quartile) as the cutoff value, patients with higher levels of saliva EGFR had worse prognosis in terms of overall survival ( P = .04). Conversely, no association was found between serum EGFR and clinical outcomes in OSCC patients. Conclusions: Saliva EGFR can be considered as a potential tumor marker for OSCC with both diagnostic and prognostic values. Serum EGFR levels, on the other hand, were lower in OSCC patients, but did not show any prognostic impact. Saliva EGFR levels are worthy of further investigation as a potential diagnostic and prognostic biomarker for OSCC. Level of Evidence: 3b. Laryngoscope, 127:E408–E414, 2017